Heat-insulating, sun-proof and self-cleaning multifunctional glass and preparation method thereof

By adopting a multi-layer structural design of modified glass substrate, photochromic insulation layer and surface functional protective layer on the window glass, the shortcomings of existing window glass in sun protection, heat insulation and self-cleaning performance are solved, and the multifunctionality of heat insulation, sun protection and self-cleaning is achieved, improving energy utilization efficiency and user experience.

CN119774893APending Publication Date: 2025-04-08李宁
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411926869.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing window glass has significant shortcomings in sun protection, insulation and self-cleaning performance, which affects the user experience and energy utilization efficiency.

Method used

The multi-layer structural design of a modified glass matrix, a photochromic thermal insulation layer and a surface functional protective layer is adopted. The photochromic thermal insulation layer is composed of gradient doping distribution of tungsten oxide nanoparticles, and the surface functional protective layer includes a superhydrophobic nanostructure layer and a self-cleaning functional layer.

Benefits of technology

It realizes the versatility of glass, heat insulation, sun protection and self-cleaning, improves energy utilization efficiency, simplifies maintenance operations, and improves user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774893A_ABST
    Figure CN119774893A_ABST
Patent Text Reader

Abstract

The present invention discloses a heat-insulating, sun-proof and self-cleaning multifunctional glass and a preparation method thereof, wherein the multifunctional glass comprises a modified glass substrate and a photochromic heat-insulating layer and a surface functional protective layer sequentially compounded on the surface of the modified glass substrate; the surface functional protective layer comprises a super-hydrophobic nanostructure layer and a self-cleaning functional layer sequentially arranged from the inside to the outside; the photochromic heat-insulating layer is a photothermal response layer with a gradient doping distribution of tungsten oxide nanoparticles, wherein the doping density of the tungsten oxide nanoparticles close to the side of the modified glass substrate is low, and the doping density of the tungsten oxide nanoparticles far from the side of the modified glass substrate is high; the super-hydrophobic nanostructure layer is mainly composed of fluorosilane-modified SiO2 nanoparticles; the self-cleaning functional layer is a TiO2 film deposited on the surface of the super-hydrophobic nanostructure layer by plasma enhanced chemical vapor deposition. Compared with the prior art, the glass of the present invention has multiple functions such as excellent heat insulation, sun protection and self-cleaning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, and in particular to a heat-insulating, sun-proof and self-cleaning multifunctional glass and a preparation method thereof. Background Art

[0002] In modern architectural design, windows are not only an important part of building lighting and ventilation, but also an important embodiment of building aesthetics. As people's requirements for living environment comfort and energy efficiency continue to increase, the functional requirements for windows are also increasing. However, while existing windows meet the requirements of aesthetics and lighting, they often have significant deficiencies in sun protection, heat insulation and self-cleaning performance, which affects the overall user experience and energy efficiency.

[0003] First of all, strong direct sunlight in summer is one of the main reasons for the sharp rise in indoor temperature. This not only increases the energy consumption of refrigeration equipment such as air conditioners, resulting in energy waste, but may also have an adverse effect on the health and comfort of residents. Although existing window designs often use technologies such as double-glazing or low-emissivity glass to improve thermal insulation performance, these measures are still difficult to effectively block high-energy solar radiation in extremely high temperature environments. In addition, in order to further reduce the rise in indoor temperature, many buildings choose to install heat-insulating sun-proof curtains or sunshades. However, these additional devices have problems such as inconvenient operation, complex maintenance, and poor aesthetics in actual use, and cannot provide an ideal solution.

[0004] Secondly, existing glass materials also have significant defects in anti-fouling and self-cleaning performance. Dust, stains and fingerprints easily accumulate on the surface of traditional glass, which not only affects the clarity of vision, but also increases the frequency and difficulty of cleaning and maintenance. Although some glass products have introduced anti-fouling coatings, these methods often have limited effects in practical applications, lack durability, and it is difficult to maintain good self-cleaning performance for a long time.

[0005] In summary, current building windows have significant deficiencies in terms of sun protection, heat insulation and self-cleaning performance, and the additional solutions are complex and inconvenient to operate. Therefore, there is an urgent need to develop a new type of multifunctional glass that can not only effectively block strong sunlight, reduce indoor temperature, and improve energy efficiency, but also have excellent anti-fouling and self-cleaning properties to simplify maintenance operations and enhance the overall user experience. Summary of the invention

[0006] The main purpose of the present invention is to provide a heat-insulating, sun-proof and self-cleaning multifunctional glass and a preparation method thereof in view of the deficiencies in the prior art, so as to solve the problems of poor heat-insulating and sun-proof performance and insufficient anti-fouling performance of existing window glass.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A heat-insulating, sun-proof and self-cleaning multifunctional glass, comprising a modified glass substrate and a photochromic heat-insulating layer and a surface functional protective layer sequentially compounded on the surface of the modified glass substrate; the surface functional protective layer comprises a super-hydrophobic nanostructure layer and a self-cleaning functional layer sequentially arranged from the inside to the outside;

[0009] The photochromic heat-insulating layer is a photothermal response layer with a gradient doping distribution of tungsten oxide nanoparticles, wherein the doping density of the tungsten oxide nanoparticles on the side close to the modified glass substrate is lower, and the doping density of the tungsten oxide nanoparticles on the side away from the modified glass substrate is higher; and the following relationship is satisfied:

[0010] C(x)=C0+αx n ;

[0011] Wherein, C(x) is the volume fraction of tungsten oxide nanoparticles at a distance x from the modified glass substrate; C0 is the minimum volume fraction of tungsten oxide nanoparticles close to the modified glass substrate side, and the value range of C0 is 0.5-0.8 vol%; α is the doping gradient coefficient, and the value range of α is 0.01-0.05 vol% / μm n ; x is the distance from the glass substrate, in μm; n is the gradient index, and the value range of n is 1.2-1.8;

[0012] The super-hydrophobic nanostructure layer is mainly composed of fluorosilane-modified SiO2 nanoparticles, with a thickness of 1-3 μm, a water contact angle of ≥150°, and a sliding angle of ≤5°; the layer provides super-hydrophobic and anti-fouling properties, effectively preventing stains and fingerprints from adhering;

[0013] The self-cleaning functional layer is a TiO2 film deposited on the surface of the super-hydrophobic nanostructure layer using plasma enhanced chemical vapor deposition (PECVD) with a thickness of 50-100nm, and then annealed at 200-300°C to obtain anatase phase TiO2; wherein the film produces a photocatalytic effect under ultraviolet light irradiation, degrading organic dirt and bacteria, so that the glass has a self-cleaning function.

[0014] Preferably, the gradient doping distribution of the tungsten oxide nanoparticles of the photochromic insulation layer is achieved by controlling the spraying process parameters, specifically: the concentration of the tungsten oxide nanoparticle suspension is controlled at 0.5-1.0wt%, the spraying solution flow rate is controlled at 0.2-0.5mL / min, the distance between the spray gun and the glass substrate surface is controlled at 100-150mm, and the gradient distribution is achieved by increasing the concentration of the tungsten oxide nanoparticle suspension by 0.05-0.1wt% for every 10μm thickness sprayed during the spraying process; after the spraying is completed, it is dried at 80-100°C for 1-2 hours to obtain a 50-100μm photochromic insulation layer.

[0015] Preferably, the photochromic heat-insulating layer comprises the following components in parts by weight: 100 parts of adhesive, 10-20 parts of tungsten oxide nanoparticles, 5-10 parts of hollow silica microspheres, 2-6 parts of ionic liquid dispersants, and 0.5-2 parts of ultraviolet absorbers; the average particle size of the hollow microspheres is 20-40 μm, and the wall thickness is 0.5-1.5 μm.

[0016] Among them, the adhesive provides a transparent bonding matrix, tungsten oxide (WO3) nanoparticles achieve photochromism (darkening rapidly under strong light conditions to block high-energy components in sunlight), hollow microspheres reduce layer density and provide scattering to enhance thermal insulation performance, ionic liquid dispersants ensure uniform distribution of nanoparticles, and UV absorbers further improve UV blocking rate.

[0017] Preferably, the modified glass matrix is ​​a glass substrate obtained by adding 0.1-0.5wt% graphene nanosheets and 0.5-1.5wt% nitrogen-doped titanium dioxide nanoparticles to low-iron float glass raw materials, melting and forming at 1550-1600°C, and annealing, and has a thickness of 4-6mm.

[0018] Preferably, the modified glass substrate is cleaned and activated after ultrasonic cleaning (40kHz frequency, cleaning in deionized water for 10-20 minutes) and plasma surface treatment (RF power of 50-100W, treatment time of 30-60 seconds) to improve the adhesion of the photochromic insulation layer.

[0019] Preferably, an electrochromic light-emitting layer is further provided between the photochromic heat-insulating layer and the surface functional protective layer, and the electrochromic light-emitting layer comprises the following components in parts by weight:

[0020] 100 parts of dynamically reversible ion-conducting polymer, 20-30 parts of electrolyte containing LiTFSI and ionic liquid, 10-20 parts of phase change material microcapsules, 5-10 parts of nanocellulose, 2-5 parts of near-infrared photosensitive initiator, and 2-4 parts of antioxidant.

[0021] Among them, the electrochromic dimming layer adopts a composite design of dynamic reversible ion-conducting polymers and phase-change material microcapsules, which not only realizes controllable electrochromic dimming, but also gives the material self-repair ability and photothermal buffering performance under microscopic damage, extending product life and improving user comfort.

[0022] Among them, the electrochromic color-changing layer realizes reversible color conversion through the action of electric field, and can adjust the visible light transmittance under external control. It cooperates with the phase change material microcapsules to provide thermal buffering and auxiliary self-repair under light and external temperature changes; the dynamic reversible ion conductive polymer makes ion migration reversible, thereby maintaining stable electrochromic performance during long-term use.

[0023] Preferably, the dynamic reversible ion-conducting polymer is prepared by reacting 4,4'-diaminoazobenzene with maleic anhydride in N,N-dimethylformamide at 60-70°C for 4-6 hours to obtain a prepolymer containing a Diels-Alder reversible addition product, and then copolymerizing the prepolymer with a crown ether unit and an imidazolyl ionic liquid group to form a polymer matrix; wherein the Diels-Alder type reversible covalent bond in the dynamic reversible ion-conducting polymer provides a reversible double ring addition structure formed by the reaction of 4,4'-diaminoazobenzene with maleic anhydride. The crown ether group and the imidazolyl ionic liquid side group can form complex ion conduction with LiTFSI; at 80-90°C, the reversible covalent bonds of the polymer open, increasing the activity of the molecular chain segments, and the covalent bonds close again when cooled to room temperature, thereby realizing the construction of a self-repairing ion conduction channel; that is, the dynamic reversible ion conduction polymer is constructed by reversible covalent bonds (such as Diels-Alder bonds) and ion action sites, which can promote chain segment movement and self-repairing ion conduction channels under heating or near-infrared light, thereby extending the service life of the electrochromic light-emitting layer;

[0024] The electrolyte containing LiTFSI and ionic liquid is an electrolyte of LiTFSI and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid, wherein the concentration of LiTFSI is 0.1-0.5 mol / L, and the amount of ionic liquid is 20-40 wt% of the total mass of the electrolyte;

[0025] The phase change material microcapsules are made of n-octadecane and n-hexadecane mixed in a mass ratio of 3:1 as the core material and polymethyl methacrylate as the shell material, and the average particle size of the microcapsules is 1-5 μm;

[0026] The nanocellulose has a length of 100-300 nm and a diameter of 5-20 nm;

[0027] The near-infrared photosensitive initiator is an iridium or platinum complex; more preferably, it is an iridium-containing complex, which can induce enhanced ion mobility under 700-1100nm near-infrared light, thereby accelerating the self-repair process in the electrochromic layer; the antioxidant is a hindered amine antioxidant.

[0028] Preferably, the preparation method of the phase change material microcapsule is:

[0029] a) mixing n-octadecane and n-hexadecane in a mass ratio of 3:1 and heating to 80°C to melt;

[0030] b) dissolving methyl methacrylate, 0.1-0.5 wt % of azobisisobutyronitrile initiator and 1,6-hexanediol dimethacrylate in deionized water, and adding 0.2-0.5 wt % of sodium lauryl sulfate as an emulsifier;

[0031] c) slowly adding the molten mixture in step a) to the solution in step b) at a rate of 0.1-0.3 mL / min, and shearing and emulsifying for 20-30 minutes at a temperature of 80° C. and a rotation speed of 5000-8000 rpm;

[0032] d) heating the emulsion to 85° C. under nitrogen protection and reacting for 3-5 hours;

[0033] e) cooling, filtering, washing and drying to obtain phase change material microcapsules with an average particle size of 1-5 μm and an encapsulation efficiency of ≥90%.

[0034] Preferably, the surface functional protective layer is also added with 1-3 parts by weight of NaYF4:Yb,Er upconversion luminescent nanoparticles with a particle size of 20-50nm; it is used to convert near-infrared light into visible light, provide additional light energy for TiO2 to enhance the self-cleaning effect under weak light, and can be used as an anti-counterfeiting mark.

[0035] Preferably, a conductive transition layer with a thickness of 2-5 μm is further provided between the electrochromic light-emitting layer and the photochromic heat-insulating layer, and the conductive transition layer comprises PEDOT:PSS and silver nanowires in a mass ratio of 100:(2-5) to improve the uniformity of electric field distribution and the electrochromic response speed.

[0036] In addition, the present invention also provides a method for preparing heat-insulating, sun-proof and self-cleaning multifunctional glass, comprising the following steps:

[0037] 1) preparing a modified glass matrix: adding 0.1-0.5wt% of graphene nanosheets and 0.5-1.5wt% of nitrogen-doped titanium dioxide nanoparticles to a low-iron content glass raw material, melting, molding and annealing at 1550-1600° C. to obtain a 4-6mm thick modified glass matrix, and performing a plasma surface activation treatment after ultrasonic cleaning;

[0038] 2) Preparation of photochromic heat-insulating layer: Adhesive, tungsten oxide nanoparticles, hollow silica microspheres, ionic liquid dispersant and ultraviolet absorber are mixed according to a ratio, the initial concentration of tungsten oxide nanoparticle suspension is 0.5wt%, and spraying is performed layer by layer at a flow rate of 0.2-0.5mL / min. The concentration of tungsten oxide is increased by 0.05-0.1wt% for each 10μm thickness sprayed until C(x)=C0+αx is satisfied. n Distribution, spraying distance is 100-150mm; after spraying, dry at 80-100℃ for 1-2 hours to obtain a 50-100μm photochromic insulation layer;

[0039] 3) Preparing a surface functional protective layer: applying 1-3 wt% fluorosilane-modified SiO2 nanoparticle suspension to the surface of the photochromic insulation layer at an immersion and pulling speed of 2 mm / s for 1-3 times, drying at room temperature for 5-10 minutes, and then heat treating at 80° C. for 30-60 minutes to form a 1-3 μm super-hydrophobic nanostructure layer;

[0040] A titanium tetrachloride and oxygen reaction gas are introduced into the super-hydrophobic nanostructure layer by plasma enhanced chemical vapor deposition at a pressure of 5-10 Pa and a radio frequency power of 50-100 W, and a TiO2 film with a thickness of 50-100 nm is deposited, and annealed at 200-300° C. for 1-2 hours to make the TiO2 present anatase phase, thereby forming a self-cleaning functional layer;

[0041] 4) Finally, the glass is annealed in an inert atmosphere at 80-90° C. for 2-4 hours, thereby completing the preparation of the heat-insulating and sun-proof multifunctional glass.

[0042] Preferably, the method further comprises at least one of the following steps a), b) and c):

[0043] a) preparing an electrochromic light-emitting layer: a dynamically reversible ion-conducting polymer, LiTFSI and an ionic liquid electrolyte, a phase change material microcapsule, nanocellulose, a near-infrared photosensitive initiator and an antioxidant are mixed in proportion, stirred at 80-90° C. in a nitrogen atmosphere for 2-4 hours, and then scraped or spin-coated on the surface of the photochromic heat-insulating layer to a thickness of 20-40 μm, and vacuum-dried at 80-100° C. for 2-4 hours to cure and form; the dynamically reversible ion-conducting polymer has a reversible covalent bond and an ion action site, so that the layer can promote segment movement and ion channel reconstruction under heating or near-infrared irradiation, thereby achieving self-repairing electrochromic performance;

[0044] b) dispersing 1-3 parts by weight of NaYF4:Yb,Er nanoparticles in TiO2 sol, stirring for 10-20 minutes, uniformly dispersing and depositing on the super-hydrophobic nanostructure layer, and curing by annealing at 150-250° C. for 1-2 hours; so that the self-cleaning functional layer can also enhance the photocatalytic activity through the upconversion effect under weak light conditions, and can be used as an anti-counterfeiting mark;

[0045] c) Preparation of a conductive transition layer: PEDOT:PSS and silver nanowires are dispersed in water at a mass ratio of 100:(2-5) with a concentration of 1-3 wt%, and spin-coated on the electrochromic dimming layer 1-3 times at 500-1000 rpm with a thickness of 2-5 μm, and annealed at 120-150° C. for 30-60 minutes to make the electrochromic dimming layer receive an electric field uniformly and improve the dimming response speed.

[0046] Compared with the prior art, the present invention has at least the following beneficial effects:

[0047] 1) The glass of the present invention adopts a multi-layer structure design of a modified glass matrix and a surface functional protective layer (super-hydrophobic nanostructure layer and self-cleaning functional layer), which together realizes the multifunctionality of heat insulation, sun protection and self-cleaning of the glass.

[0048] 2) The photochromic heat-insulating layer of the present invention is mainly composed of gradient doping distribution of tungsten oxide nanoparticles; wherein, the tungsten oxide nanoparticles can quickly change color under strong light irradiation and block the high-energy components in sunlight, achieving an effective heat-insulating effect; due to the photochromic properties of tungsten oxide, the glass can quickly darken under strong sunlight, thereby reducing heat conduction in the window. In addition, by adopting a gradient doping distribution of tungsten oxide nanoparticles (low doping on the side close to the glass substrate and high doping on the side away from the glass substrate), the heat and light isolation effect is effectively optimized by controlling the distribution density of the nanoparticles; this gradient design ensures that the glass has flexible response capabilities under different light intensities, further improving the overall heat-insulating performance of the glass.

[0049] 3) The surface functional protective layer of the present invention includes a super-hydrophobic nanostructure layer and a self-cleaning functional layer. The combination of these two layers provides excellent anti-fouling and self-cleaning capabilities for the glass. Among them, the super-hydrophobic nanostructure layer uses fluorosilane-modified SiO2 nanoparticles to give the glass super-hydrophobic properties; the water contact angle is ≥150°, the sliding angle is ≤5°, and it can effectively prevent the adhesion of stains and fingerprints even in more extreme environments; this not only enhances the anti-fouling ability of the glass, but also reduces the need for cleaning and maintenance, greatly improving the user experience. Among them, the self-cleaning functional layer uses a TiO2 film deposited by PECVD, which uses photocatalysis to decompose organic dirt and bacteria under ultraviolet light, thereby keeping the glass surface clean; the photocatalytic effect of the TiO2 film is active under light conditions, especially under ultraviolet light, which can efficiently degrade dirt and remove bacteria, effectively improving the self-cleaning function of the glass; this self-cleaning function can greatly reduce the frequency of cleaning the glass and reduce maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is a schematic diagram of the decomposed structure of glass in one embodiment of the present invention;

[0051] Figure 2 is a schematic diagram of the exploded structure of glass in another embodiment of the present invention;

[0052] Figure 3 is a schematic diagram of the exploded structure of glass in another embodiment of the present invention;

[0053] In the figure: 1. modified glass matrix; 2. photochromic heat insulation layer; 3. surface functional protection layer; 31. super-hydrophobic nanostructure layer; 32. self-cleaning functional layer; 4. electrochromic light-emitting layer; 5. conductive transition layer. DETAILED DESCRIPTION

[0054] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Please refer to the attached Figures 1 to 3 According to the first aspect of the present application, a heat-insulating, sun-proof and self-cleaning multifunctional glass is provided, comprising a modified glass substrate 1, and a photochromic heat-insulating layer 2 and a surface functional protective layer 3 which are sequentially compounded on the surface of the modified glass substrate 1; the surface functional protective layer 3 comprises a super-hydrophobic nanostructure layer 31 and a self-cleaning functional layer 32 which are sequentially arranged from the inside to the outside;

[0056] The photochromic heat-insulating layer 2 is a photothermal response layer having a gradient doping distribution of tungsten oxide nanoparticles, wherein the doping density of the tungsten oxide nanoparticles close to the modified glass substrate 1 is lower, and the doping density of the tungsten oxide nanoparticles far from the modified glass substrate 1 is higher; and the following relationship is satisfied:

[0057] C(x)=C0+αx n ;

[0058] Wherein, C(x) is the volume fraction of tungsten oxide nanoparticles at a distance x from the modified glass substrate; C0 is the minimum volume fraction of tungsten oxide nanoparticles close to the modified glass substrate side, and the value range of C0 is 0.5-0.8 vol%; α is the doping gradient coefficient, and the value range of α is 0.01-0.05 vol% / μm n ; x is the distance from the glass substrate, in μm; n is the gradient index, and the value range of n is 1.2-1.8;

[0059] The super-hydrophobic nanostructure layer 31 is mainly composed of fluorosilane-modified SiO2 nanoparticles, with a thickness of 1-3 μm, a water contact angle of ≥150°, and a sliding angle of ≤5°; this layer provides super-hydrophobic and anti-fouling properties, effectively preventing stains and fingerprints from adhering;

[0060] The self-cleaning functional layer 32 is a TiO2 film deposited on the surface of the super-hydrophobic nanostructure layer 31 using plasma enhanced chemical vapor deposition (PECVD) with a thickness of 50-100nm, and then annealed at 200-300°C to obtain anatase phase TiO2; wherein, the film produces a photocatalytic effect under ultraviolet light irradiation, degrading organic dirt and bacteria, so that the glass has a self-cleaning function.

[0061] Among them, the photochromic heat-insulating layer 2 uses a gradient doping distribution of tungsten oxide nanoparticles to achieve photothermal response regulation. Under strong light, the glass surface can quickly darken, blocking heat energy and improving the heat insulation effect; while in weak light, the glass maintains light transmittance to avoid affecting the field of vision due to excessive darkening; the gradient distribution design enables the layer to flexibly adjust the photothermal response according to the needs of different areas and improve the heat insulation performance.

[0062] Among them, the super-hydrophobic nanostructure layer 31 is mainly composed of fluorosilane-modified SiO2 nanoparticles, with a water contact angle ≥150° and a sliding angle ≤5°, which significantly improves the anti-fouling property of the glass, reduces the adhesion of stains and fingerprints, reduces the cleaning frequency, and reduces maintenance costs; its super-hydrophobicity effectively blocks sewage and oil stains, and improves the self-cleaning ability of the glass surface.

[0063] Among them, the self-cleaning functional layer 32 is a rutile phase TiO2 film deposited by plasma enhanced chemical vapor deposition (PECVD), which has a photocatalytic effect under ultraviolet light; TiO2 can decompose organic pollutants, bacteria, etc., further improving the self-cleaning ability of the glass; this layer can effectively degrade organic matter through photocatalytic reaction, keep the glass clean for a long time, and reduce maintenance frequency and cost.

[0064] In one embodiment of the present application, the gradient doping distribution of tungsten oxide nanoparticles in the photochromic insulation layer 2 is achieved by controlling the spraying process parameters, specifically: the concentration of the tungsten oxide nanoparticle suspension is controlled at 0.5-1.0wt%, the spraying solution flow rate is controlled at 0.2-0.5mL / min, the distance between the spray gun and the glass substrate surface is controlled at 100-150mm, and the gradient distribution is achieved by increasing the concentration of the tungsten oxide nanoparticle suspension by 0.05-0.1wt% for every 10μm thickness sprayed during the spraying process; after spraying, it is dried at 80-100°C for 1-2 hours to obtain a 50-100μm photochromic insulation layer 2.

[0065] In one embodiment of the present application, the photochromic insulation layer 2 includes the following components in parts by weight: 100 parts of adhesive, 10-20 parts of tungsten oxide nanoparticles, 5-10 parts of hollow silica microspheres, 2-6 parts of ionic liquid dispersants, and 0.5-2 parts of ultraviolet absorbers; the average particle size of the hollow microspheres is 20-40 μm, and the wall thickness is 0.5-1.5 μm.

[0066] Among them, the adhesive provides a transparent bonding matrix, tungsten oxide (WO3) nanoparticles achieve photochromism (darkening rapidly under strong light conditions to block high-energy components in sunlight), hollow microspheres reduce layer density and provide scattering to enhance thermal insulation performance, ionic liquid dispersants ensure uniform distribution of nanoparticles, and UV absorbers further improve UV blocking rate.

[0067] In one embodiment of the present application, the modified glass substrate 1 is a glass substrate obtained by adding 0.1-0.5wt% of graphene nanosheets and 0.5-1.5wt% of nitrogen-doped titanium dioxide nanoparticles to low-iron float glass raw materials, melting and forming at 1550-1600°C, and annealing, with a thickness of 4-6mm. Among them, the graphene nanosheets enhance the mechanical strength and thermal conductivity of the glass substrate, and improve the overall stability and durability of the glass. The nitrogen-doped titanium dioxide nanoparticles not only improve the ultraviolet blocking ability of the glass, but also improve the self-cleaning function through photocatalysis, further improving the anti-fouling performance of the glass.

[0068] In one embodiment of the present application, the surface of the modified glass substrate 1 is cleaned and activated after ultrasonic cleaning (40kHz frequency, cleaning in deionized water for 10-20 minutes) and plasma surface treatment (RF power of 50-100W, treatment time of 30-60 seconds) to improve the adhesion of the photochromic insulation layer 2.

[0069] In one embodiment of the present application, an electrochromic light-emitting layer 4 is further provided between the photochromic heat-insulating layer 2 and the surface functional protective layer 3, and the electrochromic light-emitting layer 4 includes the following components in parts by weight:

[0070] 100 parts of dynamically reversible ion-conducting polymer, 20-30 parts of electrolyte containing LiTFSI and ionic liquid, 10-20 parts of phase change material microcapsules, 5-10 parts of nanocellulose, 2-5 parts of near-infrared photosensitive initiator, and 2-4 parts of antioxidant.

[0071] Among them, the electrochromic dimming layer 4 can change the color of the glass through reversible ion migration under the action of an external electric field, and then adjust the transmittance of visible light. This function can adjust the transparency of the glass according to user needs, effectively adjust the indoor light, and improve indoor comfort; for example, it automatically darkens under strong light to enhance the heat insulation effect, and vice versa it becomes brighter to maintain light transmittance; and the electrochromic dimming layer 4 adopts a composite design of dynamic reversible ion conductive polymer and phase change material microcapsule, which not only realizes controllable electrochromic dimming, but also gives the material self-repair ability and photothermal buffering performance under microscopic damage, thereby extending the product life and improving user comfort.

[0072] Among them, the electrochromic color-changing light-emitting layer 4 realizes reversible color conversion through the action of electric field, and can adjust the visible light transmittance under external control. It cooperates with the phase change material microcapsules to provide thermal buffering and auxiliary self-repair under light and external temperature changes; the dynamic reversible ion conductive polymer makes ion migration reversible, thereby maintaining stable electrochromic performance during long-term use.

[0073] Among them, the dynamic reversible ion-conducting polymer forms a reversible covalent bond through the Diels-Alder reaction, which enables the material to promote the movement of molecular segments and the reconstruction of ion channels under heating or near-infrared light, thereby achieving self-repair; this self-repairing ability helps to improve the durability of the electrochromic layer, allowing it to maintain high performance during long-term use. In an environment with large temperature fluctuations, the phase change material microcapsules can effectively buffer the changes in heat, avoid the impact of excessive temperature differences between the inside and outside of the glass on the building, and further improve the thermal insulation performance of the window glass.

[0074] In one embodiment of the present application, the dynamic reversible ion-conducting polymer is prepared by reacting 4,4'-diaminoazobenzene with maleic anhydride in N,N-dimethylformamide at 60-70°C for 4-6 hours to obtain a prepolymer containing a Diels-Alder reversible addition product, and then copolymerizing the prepolymer with a crown ether unit and an imidazolyl ionic liquid group to form a polymer matrix; wherein the Diels-Alder type reversible covalent bond in the dynamic reversible ion-conducting polymer is provided by a bicyclic addition structure formed by the reaction of 4,4'-diaminoazobenzene with maleic anhydride Reversibility: the crown ether group and the imidazolyl ionic liquid side group can undergo complex ion conduction with LiTFSI; at 80-90°C, the reversible covalent bonds of the polymer open, increasing the activity of the molecular chain segments, and the covalent bonds close again when cooled to room temperature, thereby realizing the construction of a self-repairing ion conduction channel; that is, the dynamic reversible ion conduction polymer is constructed through reversible covalent bonds (such as Diels-Alder bonds) and ion action sites, which can promote chain segment movement and self-repairing ion conduction channels under heating or near-infrared light, thereby extending the service life of the electrochromic light-emitting layer 4;

[0075] The electrolyte containing LiTFSI and ionic liquid is an electrolyte of LiTFSI and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid, wherein the concentration of LiTFSI is 0.1-0.5 mol / L, and the amount of ionic liquid is 20-40 wt% of the total mass of the electrolyte;

[0076] The phase change material microcapsules are made of n-octadecane and n-hexadecane mixed in a mass ratio of 3:1 as core material and polymethyl methacrylate as shell material, and the average particle size of the microcapsules is 1-5 μm;

[0077] Nanocellulose has a length of 100-300nm and a diameter of 5-20nm;

[0078] The near-infrared photosensitive initiator is an iridium or platinum complex; more preferably, it is an iridium-containing complex, which can induce enhanced ion mobility under 700-1100nm near-infrared light, thereby accelerating the self-repair process in the electrochromic layer; the antioxidant is a hindered amine antioxidant.

[0079] In one embodiment of the present application, the preparation method of phase change material microcapsules is:

[0080] a) mixing n-octadecane and n-hexadecane in a mass ratio of 3:1 and heating to 80°C to melt;

[0081] b) dissolving methyl methacrylate, 0.1-0.5 wt % of azobisisobutyronitrile initiator and 1,6-hexanediol dimethacrylate in deionized water, and adding 0.2-0.5 wt % of sodium lauryl sulfate as an emulsifier;

[0082] c) slowly adding the molten mixture in step a) to the solution in step b) at a rate of 0.1-0.3 mL / min, and shearing and emulsifying for 20-30 minutes at a temperature of 80° C. and a rotation speed of 5000-8000 rpm;

[0083] d) heating the emulsion to 85° C. under nitrogen protection and reacting for 3-5 hours;

[0084] e) cooling, filtering, washing and drying to obtain phase change material microcapsules with an average particle size of 1-5 μm and an encapsulation efficiency of ≥90%.

[0085] In one embodiment of the present application, 1-3 parts by weight of NaYF4:Yb,Er upconversion luminescent nanoparticles are also added to the surface functional protective layer 3, and the particle size is 20-50nm; wherein, NaYF4:Yb,Er upconversion luminescent nanoparticles are added to the surface functional protective layer 3, and these nanoparticles can convert near-infrared light into visible light under near-infrared light irradiation, providing additional light energy for TiO2 to enhance the self-cleaning function; this not only improves the self-cleaning effect of the glass under weak light conditions, but also can serve as an anti-counterfeiting mark to improve product safety.

[0086] In one embodiment of the present application, a conductive transition layer 5 with a thickness of 2-5 μm is further provided between the electrochromic light-emitting layer 4 and the photochromic heat-insulating layer 2. The conductive transition layer 5 includes PEDOT:PSS and silver nanowires in a mass ratio of 100:(2-5) to improve the uniformity of electric field distribution and the electrochromic response speed. By optimizing the electric field effect of the electrochromic layer, its response time is shortened and the electrochromic performance is more efficient.

[0087] According to the second aspect of the present application, the present application also provides a method for preparing heat-insulating, sun-proof and self-cleaning multifunctional glass, comprising the following steps:

[0088] 1) preparing a modified glass substrate 1: adding 0.1-0.5wt% of graphene nanosheets and 0.5-1.5wt% of nitrogen-doped titanium dioxide nanoparticles to a low-iron content glass raw material, melting, molding and annealing at 1550-1600° C. to obtain a 4-6mm thick modified glass substrate 1, and performing a plasma surface activation treatment after ultrasonic cleaning;

[0089] 2) Preparation of photochromic heat-insulating layer 2: Adhesive, tungsten oxide nanoparticles, hollow silica microspheres, ionic liquid dispersant and ultraviolet absorber are mixed according to a ratio, the initial concentration of tungsten oxide nanoparticle suspension is 0.5wt%, and spraying is performed layer by layer at a flow rate of 0.2-0.5mL / min. The concentration of tungsten oxide is increased by 0.05-0.1wt% for each 10μm thickness sprayed until C(x)=C0+αx is satisfied. n Distribution, the spraying distance is 100-150mm; after spraying, dry at 80-100℃ for 1-2 hours to obtain a 50-100μm photochromic insulation layer 2;

[0090] 3) Preparing a surface functional protective layer 3: applying a 1-3 wt% fluorosilane-modified SiO2 nanoparticle suspension to the surface of the photochromic heat-insulating layer 2 at an immersion and pulling speed of 2 mm / s for 1-3 times, drying at room temperature for 5-10 minutes, and then heat-treating at 80° C. for 30-60 minutes to form a 1-3 μm super-hydrophobic nanostructure layer 31;

[0091] A titanium tetrachloride and oxygen reaction gas is introduced into the super-hydrophobic nanostructure layer 31 by plasma enhanced chemical vapor deposition at a pressure of 5-10 Pa and a radio frequency power of 50-100 W, and a TiO2 film with a thickness of 50-100 nm is deposited, and annealed at 200-300° C. for 1-2 hours to make the TiO2 present anatase phase, thereby forming a self-cleaning functional layer 32;

[0092] 4) Finally, the glass is annealed in an inert atmosphere at 80-90° C. for 2-4 hours, thereby completing the preparation of the heat-insulating and sun-proof multifunctional glass.

[0093] In one embodiment of the present application, at least one of the following steps a), b) and c) is also included:

[0094] a) preparing the electrochromic light-emitting layer 4: a dynamically reversible ion-conducting polymer, LiTFSI and ionic liquid electrolyte, phase change material microcapsules, nanocellulose, near-infrared photosensitive initiator and antioxidant are mixed in proportion, stirred at 80-90° C. in a nitrogen atmosphere for 2-4 hours, and then scraped or spin-coated on the surface of the photochromic heat-insulating layer 2 to a thickness of 20-40 μm, and vacuum dried at 80-100° C. for 2-4 hours to cure and form; the dynamically reversible ion-conducting polymer has reversible covalent bonds and ion action sites, so that the layer can promote segment movement and ion channel reconstruction under heating or near-infrared irradiation, thereby achieving self-repairing electrochromic performance;

[0095] b) dispersing 1-3 parts by weight of NaYF4:Yb,Er nanoparticles in TiO2 sol, stirring for 10-20 minutes, and then uniformly dispersing and depositing on the super-hydrophobic nanostructure layer 31, and curing by annealing at 150-250° C. for 1-2 hours; so that the self-cleaning functional layer 32 can also enhance the photocatalytic activity through the upconversion effect under weak light conditions, and can be used as an anti-counterfeiting mark;

[0096] c) Preparation of a conductive transition layer 5: PEDOT:PSS and silver nanowires are dispersed in water at a mass ratio of 100:(2-5) with a concentration of 1-3 wt%, and spin-coated on the electrochromic dimming layer 4 at 500-1000 rpm for 1-3 times with a thickness of 2-5 μm, and annealed at 120-150° C. for 30-60 minutes to make the electrochromic dimming layer 4 receive an electric field uniformly and improve the dimming response speed.

[0097] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.

[0098] Example 1

[0099] like Figure 1 As shown, a method for preparing a heat-insulating, sun-proof and self-cleaning multifunctional glass in this embodiment comprises the following specific steps:

[0100] 1) Preparation of modified glass substrate 1: 0.3wt% of graphene nanosheets (thickness 2-3nm, lateral size 0.5-1μm) and 1.0wt% of nitrogen-doped titanium dioxide nanoparticles (particle size 30-50nm) were added to low-iron float glass raw materials, melt-formed at 1580°C, and annealed to obtain a glass substrate with a thickness of 5mm; the glass substrate was cleaned with deionized water in an ultrasonic cleaner with a frequency of 40kHz for 15 minutes, and then subjected to plasma surface activation treatment for 45 seconds at a radio frequency power of 80W.

[0101] 2) Preparation of photochromic heat-insulating layer 2: preparing a mixed solution according to the following ratio: 100 parts of organosilicon-modified acrylate adhesive, 15 parts of tungsten oxide nanoparticles (particle size 40-60 nm), 8 parts of hollow silica microspheres (particle size 30 μm, wall thickness 1 μm), 4 parts of imidazole-based ionic liquid dispersant, and 1 part of benzotriazole ultraviolet absorber;

[0102] The mixed solution is sprayed on the modified glass substrate 1, and the concentration gradient of the tungsten oxide nanoparticles is controlled by a spraying process. The initial concentration of the tungsten oxide nanoparticle suspension is 0.5wt%, and the spraying is performed at a flow rate of 0.3mL / min and a spraying distance of 120mm; the tungsten oxide concentration is increased by 0.08wt% for every 10μm thickness sprayed until the distribution relationship of C(x)=0.6+0.03x1.5 is satisfied; and the mixture is dried at 90°C for 1.5 hours to obtain a photochromic thermal insulation layer 2 with a thickness of 75μm.

[0103] 3) Preparation of surface functional protective layer 3:

[0104] i) Preparation of super-hydrophobic nanostructure layer 31: 2 wt % of 1H,1H,2H,2H-perfluorodecyltriethoxysilane-modified SiO2 nanoparticles (particle size 50-80 nm) were dispersed in an ethanol solution and ultrasonically dispersed for 30 minutes; the solution was immersed and pulled up twice at a speed of 2 mm / s by a dip coating method; the solution was dried at room temperature for 8 minutes and then heat treated at 80°C for 45 minutes to form a super-hydrophobic nanostructure layer 31 with a thickness of 2 μm.

[0105] ii) Preparation of self-cleaning functional layer 32: Using the PECVD method, titanium tetrachloride (flow rate 20sccm) and oxygen (flow rate 40sccm) reaction gases are introduced at 8Pa gas pressure and 75W RF power to deposit a 80nm thick TiO2 film; annealing at 250°C for 1.5 hours to form an anatase phase structure of TiO2.

[0106] 4) Finally, the glass was annealed at 85° C. in a nitrogen atmosphere for 3 hours to complete the preparation of the multifunctional glass.

[0107] Example 2

[0108] like Figure 2 As shown, an electrochromic light-emitting layer 4 is added on the basis of Example 1, and the specific steps are as follows:

[0109] 1) preparing a dynamic reversible ion-conducting polymer: reacting 4,4'-diaminoazobenzene with maleic anhydride at a molar ratio of 1:1.2 in DMF at 65°C for 5 hours to obtain a prepolymer; copolymerizing the prepolymer with 18-crown-6 ether monomer and 1-ethyl-3-methylimidazolylpropyl methacrylate at a molar ratio of 3:1:1.

[0110] 2) Preparation of phase change material microcapsules:

[0111] a) mixing n-octadecane and n-hexadecane in a mass ratio of 3:1 and heating to 80°C to melt;

[0112] b) dissolving methyl methacrylate, 0.3 wt % of azobisisobutyronitrile initiator and 1,6-hexanediol dimethacrylate in deionized water, and adding 0.3 wt % of sodium dodecyl sulfate as an emulsifier;

[0113] c) slowly adding the molten mixture in step a) to the solution in step b) at a rate of 0.2 mL / min, and shearing and emulsifying for 25 minutes at a temperature of 80° C. and a rotation speed of 6500 rpm;

[0114] d) heating the emulsion to 85° C. under nitrogen protection and reacting for 4 hours;

[0115] e) After cooling, filtering, washing and drying, phase change material microcapsules with an average particle size of 3 μm and an encapsulation efficiency of ≥ 90% are obtained.

[0116] 3) Preparation of electrochromic light-emitting layer 4: Prepare coating slurry according to the following ratio: 100 parts of dynamically reversible ion-conducting polymer, 25 parts of LiTFSI / ionic liquid electrolyte (0.3 mol / L LiTFSI, 30 wt% ionic liquid), 15 parts of phase change material microcapsules, 8 parts of nanocellulose (length 200 nm, diameter 10 nm), 3 parts of iridium complex photoinitiator, and 3 parts of hindered amine antioxidant;

[0117] After stirring for 3 hours in a nitrogen atmosphere at 85° C., the mixture was coated on the surface of the photochromic heat-insulating layer 2 by a blade coating method with a thickness of 30 μm, and then dried in a vacuum at 90° C. for 3 hours to cure.

[0118] Example 3

[0119] like Figure 3 As shown, a conductive transition layer 5 is added on the basis of Example 2, and the specific steps are as follows:

[0120] PEDOT:PSS and silver nanowires (diameter 50nm, length 5-8μm) were dispersed in deionized water at a mass ratio of 100:3 to prepare a 2wt% dispersion; after ultrasonic dispersion for 20 minutes, the dispersion was spin-coated twice on the surface of the electrochromic light-emitting layer 4 at a speed of 800rpm, and annealed at 130°C for 45 minutes to form a conductive transition layer 5 with a thickness of 3.5μm.

[0121] Example 4

[0122] On the basis of Example 3, upconversion luminescent nanoparticles are added to the surface functional protective layer 3, and the specific steps are as follows:

[0123] 2 parts by weight of NaYF4:Yb,Er upconversion luminescent nanoparticles (particle size 35nm, doping ratio Yb:Er = 20:2mol%) were dispersed in TiO2 sol, ultrasonically dispersed for 15 minutes, and the modified TiO2 film was deposited by PECVD method and solidified by annealing at 200℃ for 1.5 hours.

[0124] Comparative Example 1

[0125] The glass only uses a modified glass substrate 1 without a photochromic heat-insulating layer 2 and a surface functional protective layer 3; wherein the modified glass substrate 1 is prepared according to the preparation method of the modified glass substrate 1 in Example 1.

[0126] Comparative Example 2

[0127] The glass only includes a modified glass substrate 1 and a surface functional protective layer 3, but does not include a photochromic heat-insulating layer 2; it is prepared according to the corresponding steps in Example 1.

[0128] The following performance tests were performed on the glasses of the embodiments and comparative examples, and the test results are shown in Table 1.

[0129] 1) Thermal insulation performance test: Use a heat flow meter to measure the heat conduction rate of the glass under sunlight, record the surface temperature change, and calculate the thermal resistance value.

[0130] 2) UV blocking rate test: Use ultraviolet light to irradiate the glass and use a UV spectrometer to measure the transmittance.

[0131] 3) Water contact angle and sliding angle test: Use a contact angle meter to measure the water contact angle and sliding angle of the glass surface to evaluate the superhydrophobic performance.

[0132] 4) Photocatalytic performance test: Under ultraviolet light source, the degradation efficiency of the self-cleaning functional layer is tested to evaluate the self-cleaning ability of the glass.

[0133] 5) Electrochromic performance test: The color change of the electrochromic luminous layer is adjusted by voltage control, and the response time and reversibility are recorded.

[0134] Table 1

[0135]

[0136] Among them, the above experimental test results are analyzed as follows:

[0137] 1) Thermal resistance and UV blocking rate: Compared with the comparative example, Examples 1 to 4 have higher thermal resistance and UV blocking rate, indicating that the photochromic thermal insulation layer and the surface functional protective layer work together to make the glass excellent in heat insulation and sun protection.

[0138] 2) Water contact angle and sliding angle: Compared with the comparative examples, the water contact angles of all embodiments are greater than 150° and the sliding angles are smaller, indicating good superhydrophobicity; while the water contact angles of comparative examples 1 to 2 are significantly lower, indicating poor hydrophobic and antifouling performance.

[0139] 3) Photocatalytic performance: Compared with the comparative example and Examples 1 to 2, the TiO2 self-cleaning functional layer of Examples 3 and 4 exhibited a higher photocatalytic degradation rate, especially the cleaning effect under ultraviolet light irradiation; and Example 4 enhanced the photocatalytic activity by adding NaYF4:Yb,Er nanoparticles, further improving the photocatalytic degradation rate, thereby improving the self-cleaning effect.

[0140] 4) Electrochromic performance: Compared with the comparative example and Example 1, Examples 2 to 4 have better dimming performance and faster response time due to the further addition of an electrochromic dimming layer; and Examples 3 and 4 further improve the response speed of the electrochromic layer by introducing a conductive transition layer, making the electrochromic dimming performance more stable.

[0141] In summary, the multifunctional glass of the present invention is significantly superior to traditional glass in terms of heat insulation, sun protection, dimming performance, hydrophobicity and self-cleaning performance; and through gradual optimization and addition of functional coatings and components, the comprehensive performance of the glass has been further improved.

[0142] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0143] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A heat-insulating, sun-proof and self-cleaning multifunctional glass, characterized in that: It comprises a modified glass substrate and a photochromic heat-insulating layer and a surface functional protective layer which are sequentially compounded on the surface of the modified glass substrate; the surface functional protective layer comprises a super-hydrophobic nanostructure layer and a self-cleaning functional layer which are sequentially arranged from the inside to the outside; The photochromic heat-insulating layer is a photothermal response layer with a gradient doping distribution of tungsten oxide nanoparticles, wherein the doping density of the tungsten oxide nanoparticles on the side close to the modified glass substrate is lower, and the doping density of the tungsten oxide nanoparticles on the side away from the modified glass substrate is higher; and the following relationship is satisfied: C(x)=C0+αx n ; Wherein, C(x) is the volume fraction of tungsten oxide nanoparticles at a distance x from the modified glass substrate; C0 is the minimum volume fraction of tungsten oxide nanoparticles close to the modified glass substrate side, and the value range of C0 is 0.5-0.8 vol%; α is the doping gradient coefficient, and the value range of α is 0.01-0.05 vol% / μm n ; x is the distance from the glass substrate, in μm; n is the gradient index, and the value range of n is 1.2-1.8; The super-hydrophobic nanostructure layer is mainly composed of fluorosilane-modified SiO2 nanoparticles, and the water contact angle of the super-hydrophobic nanostructure layer is ≥150° and the sliding angle is ≤5°; The self-cleaning functional layer is a TiO2 film deposited on the surface of the super-hydrophobic nanostructure layer by plasma enhanced chemical vapor deposition, and then annealed at 200-300° C. to obtain anatase phase TiO2.

2. The heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 1, characterized in that: The photochromic heat-insulating layer comprises the following components in parts by weight: 100 parts of adhesive, 10-20 parts of tungsten oxide nanoparticles, 5-10 parts of hollow silica microspheres, 2-6 parts of ionic liquid dispersants, and 0.5-2 parts of ultraviolet absorbers; the average particle size of the hollow microspheres is 20-40 μm, and the wall thickness is 0.5-1.5 μm.

3. The heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 1, characterized in that: The modified glass matrix is ​​prepared by adding 0.1-0.5wt% of graphene nanosheets and 0.5-1.5wt% of nitrogen-doped titanium dioxide nanoparticles into low-iron float glass raw materials, melting and molding at 1550-1600°C, and annealing to obtain the glass substrate.

4. The heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 1, characterized in that: An electrochromic light-emitting layer is also provided between the photochromic heat-insulating layer and the surface functional protective layer, and the electrochromic light-emitting layer comprises the following components in parts by weight: 100 parts of dynamically reversible ion-conducting polymer, 20-30 parts of electrolyte containing LiTFSI and ionic liquid, 10-20 parts of phase change material microcapsules, 5-10 parts of nanocellulose, 2-5 parts of near-infrared photosensitive initiator, and 2-4 parts of antioxidant.

5. The heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 4 is characterized in that: The dynamic reversible ion-conducting polymer is prepared by reacting 4,4'-diaminoazobenzene with maleic anhydride in N,N-dimethylformamide at 60-70°C for 4-6 hours to obtain a prepolymer containing a Diels-Alder reversible addition product, and then copolymerizing the prepolymer with a crown ether unit and an imidazole-based ionic liquid group to form a polymer matrix; The electrolyte containing LiTFSI and ionic liquid is an electrolyte of LiTFSI and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid, wherein the concentration of LiTFSI is 0.1-0.5 mol / L, and the amount of ionic liquid is 20-40 wt% of the total mass of the electrolyte; The phase change material microcapsules are made of n-octadecane and n-hexadecane mixed in a mass ratio of 3:1 as the core material and polymethyl methacrylate as the shell material, and the average particle size of the microcapsules is 1-5 μm; The nanocellulose has a length of 100-300 nm and a diameter of 5-20 nm; The near-infrared photosensitive initiator is an iridium or platinum complex; the antioxidant is a hindered amine antioxidant.

6. The heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 4, characterized in that: The preparation method of the phase change material microcapsule is as follows: a) mixing n-octadecane and n-hexadecane in a mass ratio of 3:1 and heating to 80°C to melt; b) dissolving methyl methacrylate, 0.1-0.5 wt % of azobisisobutyronitrile initiator and 1,6-hexanediol dimethacrylate in deionized water, and adding 0.2-0.5 wt % of sodium lauryl sulfate as an emulsifier; c) slowly adding the molten mixture in step a) to the solution in step b) at a rate of 0.1-0.3 mL / min, and shearing and emulsifying for 20-30 minutes at a temperature of 80° C. and a rotation speed of 5000-8000 rpm; d) heating the emulsion to 85° C. under nitrogen protection and reacting for 3-5 hours; e) cooling, filtering, washing and drying to obtain phase change material microcapsules with an average particle size of 1-5 μm and an encapsulation efficiency of ≥90%.

7. The heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 1, characterized in that: The surface functional protective layer is also added with 1-3 parts by weight of NaYF4:Yb,Er upconversion luminescent nanoparticles, and the particle size is 20-50nm.

8. The heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 4, characterized in that: A conductive transition layer with a thickness of 2-5 μm is also arranged between the electrochromic light-emitting layer and the photochromic heat-insulating layer. The conductive transition layer includes PEDOT:PSS and silver nanowires, and the mass ratio thereof is 100:(2-5).

9. A method for preparing the heat-insulating, sun-proof and self-cleaning multifunctional glass according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) preparing a modified glass matrix: adding 0.1-0.5wt% of graphene nanosheets and 0.5-1.5wt% of nitrogen-doped titanium dioxide nanoparticles to a low-iron content glass raw material, melting, molding and annealing at 1550-1600° C. to obtain a 4-6mm thick modified glass matrix, and performing a plasma surface activation treatment after ultrasonic cleaning; 2) Preparation of photochromic heat-insulating layer: Adhesive, tungsten oxide nanoparticles, hollow silica microspheres, ionic liquid dispersant and ultraviolet absorber are mixed according to a ratio, the initial concentration of tungsten oxide nanoparticle suspension is 0.5wt%, and spraying is performed layer by layer at a flow rate of 0.2-0.5mL / min. The concentration of tungsten oxide is increased by 0.05-0.1wt% for each 10μm thickness sprayed until C(x)=C0+αx is satisfied. n Distribution, spraying distance is 100-150mm; After spraying, dry at 80-100°C for 1-2 hours to obtain a 50-100 μm photochromic heat insulation layer; 3) Preparing a surface functional protective layer: applying 1-3 wt% fluorosilane-modified SiO2 nanoparticle suspension to the surface of the photochromic insulation layer at an immersion and pulling speed of 2 mm / s for 1-3 times, drying at room temperature for 5-10 minutes, and then heat treating at 80° C. for 30-60 minutes to form a 1-3 μm super-hydrophobic nanostructure layer; A titanium tetrachloride and oxygen reaction gas are introduced into the super-hydrophobic nanostructure layer by plasma enhanced chemical vapor deposition at a pressure of 5-10 Pa and a radio frequency power of 50-100 W, and a TiO2 film with a thickness of 50-100 nm is deposited, and annealed at 200-300° C. for 1-2 hours to make the TiO2 present anatase phase, thereby forming a self-cleaning functional layer; 4) Finally, the glass is annealed in an inert atmosphere at 80-90° C. for 2-4 hours, thereby completing the preparation of the heat-insulating and sun-proof multifunctional glass.

10. The method for preparing the heat-insulating, sun-proof and self-cleaning multifunctional glass according to claim 9, characterized in that: It also includes at least one of the following steps a), b) and c): a) preparing the electrochromic light-emitting layer: mixing a dynamic reversible ion-conducting polymer, LiTFSI and an ionic liquid electrolyte, a phase change material microcapsule, nanocellulose, a near-infrared photosensitive initiator and an antioxidant in proportion, stirring at 80-90° C. in a nitrogen atmosphere for 2-4 hours, then scraping or spin-coating the mixture on the surface of the photochromic heat-insulating layer to a thickness of 20-40 μm, and drying the mixture under vacuum at 80-100° C. for 2-4 hours to cure the mixture; b) dispersing 1-3 parts by weight of NaYF4:Yb,Er nanoparticles in TiO2 sol, stirring for 10-20 minutes, uniformly dispersing and depositing on the super-hydrophobic nanostructure layer, and curing by annealing at 150-250° C. for 1-2 hours; c) Preparation of conductive transition layer: PEDOT:PSS and silver nanowires are dispersed in water at a mass ratio of 100:(2-5) with a concentration of 1-3 wt %, and spin coated on the electrochromic light-emitting layer at 500-1000 rpm for 1-3 times with a thickness of 2-5 μm, and annealed at 120-150° C. for 30-60 minutes.

Citation Information

Cited By

  • Heat insulation film for hollow glass and preparation method of heat insulation film

    CN120904508A

  • Intelligent starry sky glass as well as preparation method and application thereof

    CN121559787A